Impact of Ragweed Pollen Daily Release Intensity on Long-Range Transport in Western Europe - Laurent Menut; Dmitry Khvorostyanov; Florian Couvidat; Frédérik Meleux (Atmosphere, 2021)
This study is dedicated to improving the daily release of ragweed pollen emission in the context of deterministic regional modelling for analysis and forecast. First, correlations are calculated between daily modelled meteorological variables (wind speed, temperature, humidity, precipitation, surface fluxes) and daily pollen counts at nine stations in Hungary, Croatia and France between 2005 and 2011. The 2 m temperature is the most correlated parameter, followed by convective velocity and incoming shortwave radiation, while precipitation rate and 2 m specific humidity act as limiting factors. Using these results, a ragweed pollen daily release formulation is proposed. This formulation is implemented in the CHIMERE chemistry-transport model and tested during the whole year of 2010. Results are compared to observations, and it is shown that the new formulation provides a more realistic day-to-day variability: the spatio-temporal correlation between surface measurements and modelled concentrations is 0.77, greater than two other known emission schemes.